Three New Species and a New Record of Murdannia (Commelinaceae) for the Flora of Laos - Anousone Sengthong; Surapon Saensouk; Piyaporn Saensouk; Kajonesuk Phengmala; Thawatphong Boonma; Phetlasy Souladeth (Horticulturae)
The genus Murdannia Royle was recognized as a member of the family Commelinaceae, known for its beautiful and outstanding flowers, which made it highly valued as an ornamental plant. In this study, three previously unidentified species of Murdannia are described as new species from Laos including Murdannia maronea, M. rhizomatosa, and M. thyrsoidea. Detailed descriptions, illustrations, phenology, and distribution of each species are provided, along with notes on their horticulture. Murdannia clandestina is reported as a new record for Laos. These four species of Murdannia are notable for their attractive flowers, particularly M. thyrsoidea, which was characterized by its large inflorescence, enhancing its potential as an ornamental plant. The pollen morphology of these four Murdannia species is described for the first time. The pollen grains share similar characteristics, being monads, medium-sized, bilaterally symmetrical, and prolate in shape, with a monocolpate aperture and verrucate exine sculpturing. These findings provided valuable insights to support future breeding efforts aimed at enhancing their ornamental value.